KINDS OF RATINGS OF EDUCATION RELATED SCIENTIFIC JOURNALS - Natela N. Kvelidze-Kuznetsova; Vladimir V. Laptev; Svetlana A. Morozova (Высшее образование в России)
When publishing an education related article, a problem of choosing and evaluating a scientific periodical rises. A simple comparison of educational journals ranks in Russian ratings and other resources that use an appropriate approach in selection and assessment of journals, which allows them to rate journals, shows ambiguous results. The conducted analysis revealed that none of resources offers a full range of reputable journals in an analyzed category, thus, cannot be a universal tool in this field.